2020
DOI: 10.3390/app10124188
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Impacts of Passive Cooling Techniques on Building Energy Performance: A Residential Case in Hong Kong

Abstract: Environmental concerns and growing energy costs raise the importance of sustainable development and energy conservation. The building sector accounts for a significant portion of total energy consumption. Passive cooling techniques provide a promising and cost-efficient solution to reducing the energy demand of buildings. Based on a typical residential case in Hong Kong, this study aims to analyze the integration of various passive cooling techniques on annual and hourly building energy demand with whole build… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 43 publications
0
20
0
1
Order By: Relevance
“…There are also some other strategies to support sustainable hotel building operation. In addition to promoting eco-friendly energy systems and design (e.g., [6,7]), various em-pirical studies have examined behaviour-driven energy conservation in family (e.g., [8,9]), office [10], and campus buildings [11] and reported that interventions, such as normative setting and energy-saving tips, can reduce building energy demand by 10-25% [12,13]. As guests tend to consume even more energy in hotels than at home [14], promoting conservation behaviours among hotel guests could be another promising energy-saving and carbon-reduction strategy in the hospitality industry.…”
Section: Introductionmentioning
confidence: 99%
“…There are also some other strategies to support sustainable hotel building operation. In addition to promoting eco-friendly energy systems and design (e.g., [6,7]), various em-pirical studies have examined behaviour-driven energy conservation in family (e.g., [8,9]), office [10], and campus buildings [11] and reported that interventions, such as normative setting and energy-saving tips, can reduce building energy demand by 10-25% [12,13]. As guests tend to consume even more energy in hotels than at home [14], promoting conservation behaviours among hotel guests could be another promising energy-saving and carbon-reduction strategy in the hospitality industry.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, energy consumption is closely related to greenhouse gas (GHG) emissions as well as a series of environmental pollution. In addition to developing novel energy-efficient techniques [2], in the last few decades, governments have paid much attention to efficient energy consumption and resource conversation. More and more governments implement policies to encourage business owners and households to use equipment with higher energy efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Buildings are energy-intensive structures made from construction materials, the production of which is generally hazardous to the environment [ 3 ]. Buildings are regarded as shelters and designed for thermal comfort, especially in regions with harsher climates [ 4 , 5 ], and the thermal fluctuations that are frequent occurrences in these regions resulted in increased energy consumption per building via its respective internal thermal regulation systems (air-conditioners and heaters) [ 6 , 7 ]. Passive insulation systems are seen as a less energy-intensive option for buildings in harsher climates, which has the net benefit of decreasing energy costs and being eco-friendly [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%